PENINGKATAN KEMAMPUAN MAHASISWA UKM SENI MIFTAHUL MIDAD DALAM MENULIS KARYA SASTRA PUISI MENGGUNAKAN MODEL PRAKTIK DAN LATIHAN TERBIMBING - Diyah Mahmawati; Andika Pratama Setiawan (Mastery: Master of English Language Journal, 2024)
Classroom Action Research entitled Improving the Ability of STIT Miftahul Midad Arts UKM Students in Writing Poetry Literature Using Practice Models and Guidance Exercises carried out in two cycles has been declared complete both individually and classically as expected, an indication of this improvement is seen in the pre-action percentage of 33.3% increasing to 58 .3% in cycle 1 and increased again to 91.6% in cycle 2. The method used was the practice method and guidance exercises. The subjects studied were the students of Art UKM STIT Miftahul Midad Lumajang in the 2023/2024 academic year with a total of 21 students. This research data was collected using observation and test methods which were then analyzed using quantitative descriptive techniques. With this increase, it is concluded that the use of practice methods and guidance exercises can improve the ability to write poetryof the students of Art UKM STIT Miftahul Midad Lumajang.